A survey on clinical decision support systems concerning quality of life - Reis, Luis Paulo (2019)
As a result of improved living conditions and the progress achieved in areas related to medicine, there is a decrease in the mortality rate but an increase in the number of patients with chronic diseases. Contrary to what happened until a few decades ago, patients with chronic diseases now have a high life expectancy. However, the patients increased life expectancy, often causes great pain and significant adverse effects. In addition to prolonging life, it is essential to increase the quality of life (QoL) of patients. The QoL is now considered an important aspect in clinical practice for patients with chronic illnesses, but the methods to assess QoL, in automatic or semi-automatic manners and their use in clinical decision support are still underexplored and their applications are virtually non-existent. This paper presents an overview of research related to health quality of Life, estimation of quality of life including its continuous estimation, modeling and behavioral recognition and representation of knowledge in this area and decision support systems for clinical decision making and quality of life related applications.